Eksperimentasi Problem Based Instruction (PBI) DenganOpen Ended Dan Closed Ended Ditinjau Dari KemampuanAwal Terhadap Prestasi Belajar Pada Materi LingkaranSiswa Kelas VIII Semester Genap SMP Negeri 1 SukodonoTahun Ajaran 2014/2015 - , Wulandari; , Prof. Budi Murtiyasa, M. Kom (2015)
The purpose of the research are to analysis: (1) contribution problem based instruction with open ended and closed ended direct learning in mathematics achievement (2) contribution prior knowledge direct learning in mathematics achievement (3) interaction problem based instruction with open ended and closed ended in terms of prior knowledge direct learning in mathematics achievement.The research used quasi experimental method. The population of this research was all of the class VIII student at SMP Negeri 1 Sukodono regency on academic year 2014/2015. The sample of research were by using the stratified cluster random sampling. The sample were used consist of two classes, which VIII A as experimental class 1 and VIII C as the experimental class 2. The collection data was conduted by test. The technique of analysis data consist of conditional test and hipotesis test. Conditional test consist of normality test, homogeneity test and t-matching test. The hypothesis test used unbalance two ways analysis of variance. From The Analysis, it is found that :(1) There was contribution problem based instruction with open ended and closed ended direct learning in mathematics achievement (2) There was constribution prior knowledge direct learning in mathematics achievement (3) there was not interaction problem based instruction with open ended and closed ended in terms of prior knowledge direct learning in mathematics achievement